Big Five Personality Types as Predictors of Gratitude Among Adults - Dr. Sajid Mahmood Alvi; Dr. Noman Aftab; Saira Bano (Journal of Management Practices, Humanities and Social Sciences, 2022)
The present study was aimed to examine the role of personality types on the prediction of gratitude among adults. The gender differences in gratitude were also examined. Gratitude Questionnaire-Six Item Form (GQ - 6) (McCullough, Emmons & Tsang, 2002) and Big Five personality inventory (John & Srivastava, 2005) were used for data collection for a sample of adults (N = 200). Independent t-test, Pearson Correlation, and multiple regression were computed for data analysis. Results indicated that extraversion has a significant positive correlation with agreeableness, openness, conscientiousness, and gratitude and a significant negative correlation with neuroticism. Results also showed that openness has a significant correlation with conscientiousness and gratitude and a significant negative correlation with neuroticism. Also, conscientiousness has a significant correlation with gratitude and a non-significant negative correlation with neuroticism. Neuroticism has a significant negative correlation with gratitude. Multiple regression analysis was computed with personality types as predictor variables and gratitude as an outcome variable. Findings also indicated that extroversion, agreeableness, openness, and conscientiousness have a significant positive effect on gratitude, while neuroticism has a significant negative effect on gratitude. Therefore, individuals who are social, outgoing open, and helping they inclined to show more gratitude.